Market mechanisms in public service provision - Blöchliger, Hansjörg (OECD Publishing, 2018)
This paper compares and analyses the use of market mechanisms in core sub-central policy areas, namely education, health care, transport, social protection, and environment. Arrangements like tendering, outsourcing, user choice and competition, user fees and performance-related funding can help to improve quality of service provision or lower its cost. With around 32% of total public expenditure and often wide-ranging spending powers, sub-central governments (SCG) have considerable leeway for improving their services by relying on market mechanisms. The decentralised and often fragmented nature of sub-central government poses some special challenges to efficient arrangements, however, and may require central government support or stronger inter-jurisdictional co-operation. And while market mechanisms are being harnessed ever more broadly, limits to a more extensive use have become apparent, particularly in the potential trade-off between greater efficiency and equity objectives, or between efficiency and sub-central accountability..
Keywords: Taxation